Formulation, Development, and Evaluation of Sustained Release Tablet of Ambroxol Hydrochloride (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Ambroxol hydrochloride tablet was formulated as sustained release tablets employing rice bran waxpolymer and the sustained release behavior of the fabricated tablets were investigated. Materials and Methods: Theobjectives of study are Sustained release matrix tablets containing 75 mg ambroxol hydrochloride were developedusing different drug polymer ratios of MCC, RBW and DCP. Tablets were prepared by direct compression.Formulation was optimized on the basis of acceptable tablet properties and in vitro drug release and by using23 factorial designs. Result and Discussion: The resulting formulation produced robust tablets with optimumhardness, consistent weight uniformity and low friability. All tablets but one exhibited gradual and near-completionsustained release for ambroxol hydrochloride, and 98-103% released at the end of 8 h. Conclusion: The results ofdissolution studies indicated that formulation F7, the most successful of the study, exhibited drug release patternvery close to theoretical release profile. A decrease in release kinetics of the drug was observed on increasingpolymer ratio. Applying exponential equation, all the formulation tablets (except F7) showed diffusion-dominateddrug release. The mechanism of drug release from F7 was diffusion with erosion.